Answer:
True
Step-by-step explanation:
Cant really provide step by step per se.
From left to right it’s 1, 49, 9, 70
Answer: 2x+4+3(2x-1) is not equivalent to 8x-2. it is equivalent to 8x+1
Step by step solution:
Step 1 :
Equation at the end of step 1 :
(2x + 4) + 3 • (2x - 1)
Step 2 :
Final result :
8x + 1
<span>Just graph the function up to and/or including the points indicated.
- if you have a piecewise function defined as y=x when x < 0
y=-x when x >=1
You would graph y=x from the negative direction up to 0 (but leaving an open circle on 0 because the function is not defined there
Then start at point 1 (this time with a closed circle because y=-x is defined at 1, and graph y=-x.</span>
Answer:
x/9
Step-by-step explanation:
x divided by 9
=> x ÷ 9
<em>Take that and turn it into a fraction</em>
=> x/9
hope this helps and is right. p.s. i really need brainliest :)